A study on vitamin D status among orthopaedic patients - Santhanagopal, Srinivasalu; Sebastian, Matthew; Muniswamy, Madan Mohan; Pilar, Anoop (International Journal of Research in Orthopaedics, 2020)
Background: There is an alarmingly high prevalence of hypovitaminosis D in orthopaedic patients, regardless of whether or not, they require surgical intervention. Vitamin D plays an essential role in bone formation, maintenance, and remodelling, as well as muscle function and deficiency could affect adversely in multiple ways. Many reports recently demonstrated high rates of vitamin D deficiency, in numerous segments of Indian population, but there is no study reported so far from India, which focuses specifically on vitamin D status in orthopaedic patients. Methods: It is a descriptive study to estimate vitamin D levels in patients scheduled to undergo orthopaedic surgery. Vitamin D, calcium, phosphorus and alkaline phosphatase (ALP) levels in 310 patients, who were admitted at our institution, from December 2015 to August 2017 were measured. Results: Out of 310 patients included in our study, 189 (61%) were males and 121 (39%) females. Vitamin D deficiency (<20 ng/ml) was present in 232 patients, insufficiency (<30 ng/ml) was present in 63 patients and only 15 patients had desirable levels (>30 ng/ml). Patients younger than 60 years and males had more prevalence of Vitamin D abnormality. 168 (72.4%) of the patients, with deficiency presented in winter, compared to 64 (27.6%) in summer. Conclusions: Statistically significant vitamin D deficiency was seen during winter months, in patients undergoing hip hemiarthroplasty, and in patients admitted for degenerative disease of the spine, hip and knee. Screening and treating hypovitaminosis D appears to be important in orthopaedic patients as vitamin D deficiency is prevalent across all age groups in the population studied.